C."iminal law as the last and the least resort - Hussein Gholami (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2012)
Defining the scope of criminal law and legitimated level ofintervention through criminal law over the rights and freedom ofcitizens as the most serious kind of such intervention, is a complicatedand difficult matter. The principle of criminal law as the last and theleast resort as a basic principle of this knowledge, technique andinstrument of social control, as emphasizes upon the destructiveresults of abuse of penal concepts, instruments and institutions, tries todetennine the appropriate level of intervention through criminal lawand provide the possibility of usage for other kinds of social controlinstruments and institutions. This article, as emphasizes upon thenecessity of considering this principle in more details, will discuss theconcepts, basics and implications of this principle for penal policy(criminalization and penalization).